ANALYSIS OF DROUGHT-TOLERANT GENOTYPES IN SORGHUM USING MULTIVARIATE ANALYSIS TECHNIQUES - Abdulhamed , Zeyad A.; Abood, Nihad M.; Obiad, Husam M.; Mohmood, Rawea M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted during the spring and fall seasons of 2024. The results showed a significant positive correlation between the three indices and productivity under both drought stress conditions (Ys) and non-stress conditions (Yp). This indicates that these indices are effective in identifying Genotype with high productivity potential in both scenarios. In the spring season, the superior Genotype were G7 (Giza 113), G14 (ACSAD 51), G15 (ACSAD 56), G20 (ACSAD 62), and G23 (ACSAD 66). In fall season, the top-performing Genotype were G8 (Tabet), G10 (Uruk), G17 (ACSAD 47), G20 (ACSAD 58), and G25 (ACSAD 68). All these Genotype demonstrated drought tolerance with high productivity under both stressed and non-stressed conditions. The indices used in this study help in identifying Genotype with a high ability to withstand drought, thus enhancing their effectiveness in challenging environmental conditions. Additionally, the aforementioned Genotype are considered suitable for use in crop improvement programs in the central region of Iraq, due to their ability to adapt to drought conditions and maintain good productivity under varying circumstances.